PERSON-ENVIRONMENT FIT OF THE HEARING-IMPAIRED STUDENTS IN MALAYSIAN POLYTECHNICS: A PRELIMINARY ANALYSIS (Proceedings of International Conference on Special Education, 2015)
Research in the Person-Environment fit (P-E fit) framework suggested that congruence between students’ personality types and their academic major selection is crucial for students’ satisfaction and their academic achievements but little research has been done on the hearing-impaired population. In order to enhance our understanding of P-E fit among the hearing-impaired students, this preliminary analysis examined the types of personality types based on Holland’s Typology Theory (1973, 1985). A sample of hearing-impaired students undergoing their Special Skills Certificate in 4 Polytechnics all across Malaysia were selected (N=26). Samples consisted of second and fourth semester students of June 2014 intake. Personality types were measured using an adapted Malay version of Holland’s Self Directed Search-Form E (SDS-E). Signlanguage interpreter and individual assistance were also provided to accommodate their special needs. In addition, picture-based assistance on certain items was also provided to accommodate their limited reading ability. Findings on students’ personality types and their academic major selection based on Holland Typology were discussed. The findings also imply that with certain modification and accommodation, SDS-E is valid and reliable to be used in order to understand the personality types of the hearing impaired students in Malaysian Polytechnics. Furthermore, this preliminary analysis provides insights into the largely unstudied question of how hearing-impaired personality typology and their academic major selection relate to students’ academic achievements in Malaysian Polytechnics. For a start, it is recommended that an established academic major selection system is required to provide good match between the students’ personality types and the academic major offered; thus leading to effective learning process and increase students’ outcomes.